Estudio de la deserción estudiantil de la Licenciatura en Ciencias Naturales y Educación Ambiental de la Universidad de Córdoba-Colombia- 2011 – 2015 - Flórez-Nisperuza, Elvira Patricia; Carrascal-Padilla, Joe Jair (Revista Científica, 2016)
One of the main problems facing the Colombian Higher Education System concerns high levels of dropout in the undergraduate program, the degree program in Natural Sciences and Environmental Education, Faculty of Education and Human Sciences of the University of Cordoba, Is foreign to this reality. In relation to this problem, the purpose of this research was to characterize and describe the factors that influence the dropout of the program in the period 2011 - 2015. The research was of mixed nature, interviews and surveys were applied to the sample. It is concluded that the factors that influence this phenomenon are the economic factor, lack of vocational guidance, lack of motivation, city change and paternity, to a lesser extent. Finally, this study ends with the proposal of strategies that help to mitigate the problem of desertion, based on the voices of teachers, students, managers and administrators of the program.